Acute traumatic injury of the thoracic aorta with pseudoaneurysm after blunt chest trauma: report of two cases - Mohd Yusof, Mubarak; Che Mohamed, Siti Kamariah; Hassan, Haida; Shamsudin, Sharini (Pakistan Medical Association Rawalpindi Islamabad branch, 2012)
Acute injury to the thoracic aorta is a life-threatening and can lead to various types of aortic injury including the formation of false aneurysm or pseudoaneurysm. We report two cases of acute traumatic aortic injury after motor vehicle accidents. One case had a saccular pseudoaneurysm and another case had complex aortic injury with pseudoaneurysms. We review the chest radiograph and CT scan findings.